Influence of AcCdc42-overexpressing strain individual inoculation on volatile profile in fermentation of liquid-state malt yeast agar and dark tea soup - Jie Wang; Zhenglin Fei; Changfa Yang; Rui Zhang; Junren Xu; Yaya Yuan; Caiyan Tang; Qilan Hu; Zhonghua Liu; Mingzhi Zhu; Yongyi Ge (Food Chemistry: Molecular Sciences)
The sexual developmental process of Aspergillus cristatus contributes to the unique “arohid flavor” of Fu brick tea. We hypothesize that the AcCdc42 involved in sexual development is functionally associated with the biosynthesis of volatile compounds during dark tea broth fermentation. Overexpression of the AcCdc42 resulted in the darker color of colony, larger of cleistothecium and more of ascospores in Aspergillus cristatus. Liquid MYA (Malt Yeast Agar) and dark tea soup were inoculated separately with OE::AcCdc42 and wild-type (WT) strains. Volatile profiles were analyzed by headspace solid-phase microextraction-gas chromatography–mass spectrometry and chemometrics. 41 and 31 different volatile metabolites were tentatively identified in the MYA and dark tea soup fermentation broths, respectively. In the context of relative changes, the total profile of differential volatile metabolites in the MYA fermentation broth of OE::AcCdc42 was 0.23 times higher than that of WT; and the largest changes in profile were Alcohol and Aromatic compoud, which increased by 6.05 times and decreased by 4.67 times than that of WT, respectively. The total profile of differential volatile metabolites in the dark tea soup fermentation broth of OE::AcCdc42 was 3.20 times higher than that of WT; and the largest changes in profile were Phenols and Terpene, which increased by 137.34 times and decreased by 2.38 times than that of WT, respectively. This study allows clarification the function of AcCdc42 in the process of sexual reproduction and its influence on volatile profile in liquid fermented MYA and dark tea soup.